Las Unidades Vecinales en América Latina – 1930-1970 Política, bienestar y vivienda como proyecto moderno (2014)
This research, which was developed between the second semester of 2007 and the second semester of 2013, is presented as a thesis to qualify for the title of Doctor of Architecture and is part of the Research line History of Latin American architecture of the 20th Century of PhD program in Art and Architecture of the National University of Colombia. It was conceived as the extension of studies conducted on issues of state housing of the twentieth century in Colombia and the revision of the CINVA Archive - Inter-American Center for Housing and Planning - which rests in the same University. The subject of the thesis is "the neighborhood units in Latin America" conceived as urban planning lessons, both for the architects themselves and for the community and governments." 2 Its presence, thanks to the combination of different factors: social, political, architectural and technical, phenomena an urban and social phenomenon of great magnitude and enormous importance in the history of Latin American architecture. There are two types: specific neighborhood units and private initiatives with certain commercials. This study was conducted on the first and without any interest in the second.